Hubungan Pengetahuan Ibu Tentang Pemberian Makanan Bayi dan Anak (PMBA) dengan Status Gizi Bayi Bawah Dua Tahun (Baduta) - Fatimah Sari (LPPM STIKES Guna Bangsa Yogyakarta, 2018)
Background: The paradigm of the first 1000 days of life is the period of conception and giving opportunities in saving the lives and future of children. Breast milk is recommended as one of the exclusive source of nutrition in the first 6 months. Nutrition deficiency is suspected due to a lack of understanding of parents on proper nutritious food or due to the influence of advertising. They want to break the cycle of malnutrition that causes stunting.